Interaction of 2′, 3′-cAMP with Rbp47b Plays a Role in Stress Granule Formation. Issue 1 (4th April 2018) - Kosmacz, Monika; Luzarowski, Marcin; Kerber, Olga; Leniak, Ewa; Gutiérrez-Beltrán, Emilio; Moreno, Juan Camilo; Gorka, Michał; Szlachetko, Jagoda; Veyel, Daniel; Graf, Alexander; Skirycz, Aleksandra
Abstract : 2′, 3′-cAMP associates with Arabidopsis Rbp47b and plays a role in stress granule formation. Abstract: 2′, 3′-cAMP is an intriguing small molecule that is conserved among different kingdoms. 2′, 3′-cAMP is presumably produced during RNA degradation, with increased cellular levels observed especially under stress conditions. Previously, we observed the presence of 2′, 3′-cAMP in Arabidopsis ( Arabidopsis thaliana ) protein complexes isolated from native lysate, suggesting that 2′, 3′-cAMP has potential protein partners in plants. Here, affinity purification experiments revealed that 2′, 3′-cAMP associates with the stress granule (SG) proteome. SGs are aggregates composed of protein and mRNA, which enable cells to selectively store mRNA for use in response to stress such as heat whereby translation initiation is impaired. Using size-exclusion chromatography and affinity purification analyses, we identified Rbp47b, the key component of SGs, as a potential interacting partner of 2′, 3′-cAMP. Furthermore, SG formation was promoted in 2′, 3′-cAMP-treated Arabidopsis seedlings, and interactions between 2′, 3′-cAMP and RNA-binding domains of Rbp47b, RRM2 and RRM3, were confirmed in vitro using microscale thermophoresis. Taken together, these results (1) describe novel small-molecule regulation of SG formation, (2) provide evidence for the biological role of 2′, 3′-cAMP, and (3) demonstrate an original biochemical pipeline for the identification of protein-metabolite interactors.